2015
DOI: 10.1021/acs.nanolett.5b00910
|View full text |Cite
|
Sign up to set email alerts
|

In-Plane Anisotropy in Mono- and Few-Layer ReS2 Probed by Raman Spectroscopy and Scanning Transmission Electron Microscopy

Abstract: Rhenium disulfide (ReS2) is a semiconducting layered transition metal dichalcogenide that exhibits a stable distorted 1T phase. The reduced symmetry of this system leads to in-plane anisotropy in various material properties. Here, we demonstrate the strong anisotropy in the Raman scattering response for linearly polarized excitation. Polarized Raman scattering is shown to permit a determination of the crystallographic orientation of ReS2 through comparison with direct structural analysis by scanning transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
480
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(524 citation statements)
references
References 31 publications
36
480
1
1
Order By: Relevance
“…Angle-dependent Raman scattering measurements of these samples show strong anisotropy in the 214 cm −1 peak intensity with clear twofold symmetry, as seen in recent reports [9,17,18].…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…Angle-dependent Raman scattering measurements of these samples show strong anisotropy in the 214 cm −1 peak intensity with clear twofold symmetry, as seen in recent reports [9,17,18].…”
Section: Methodssupporting
confidence: 82%
“…This opens the exciting prospect to achieve optoelectronic functionality from bulk ReX 2 of a form that can only be realized by complex fabrication of single-layer samples and devices in group VI semiconducting TMDCs. Coupled with a pronounced anisotropy in their measured optical and electrical properties [7][8][9][10], ReX 2 materials are therefore important compounds for expanding the functionality of the TMDC class, and they have potential for next-generation technologies [11,12]. The electronic structure underpinning their striking optoelectronic properties, however, remains almost completely unexplored experimentally to date.…”
Section: Introductionmentioning
confidence: 99%
“…Chenet et al [14] examined the cleaved edges of mono-and few-layer ReS2 samples by using Raman spectroscopy, and confirmed that in many cases the edges were parallel to b-axis. L. Hart et al [15] also found similar phenomenon that the crystallographic b-axis of ReS2 flakes frequently formed the longer edge of cleaved crystals, clearly indicating larger appearance probability for b-axis than a-axis.…”
Section: Resultsmentioning
confidence: 92%
“…Furthermore, polarized Raman characterization was implemented to explore the polarization dependence due to the reduced symmetry of the orthorhombic phase. The authors inspected that the orthorhombic phase SnS nanosheets exhibit strong anisotropic Raman response similar with black phosphorous150 and ReS 2 151, 152, 153, 154. The parallel‐polarization configuration strongly suggests that the A 1g mode (190.7 cm −1 ) can be employed to detect crystallographic orientation of the SnS flakes because of the A 1g mode reaches the maximum as illumination light polarization is parallel to armchair direction of the SnS flakes, which may also exist in other group IV orthorhombic phases such as SnSe, GeS, and GeSe.…”
Section: Preparation Methods and Characterizationsmentioning
confidence: 99%